Influence of the home visit programme on the functional abilities and quality of life of people with spinal cord injury in Thailand - P. Chinchai (2018)
Despite an increasing number of people with spinal cord injuries (SCI) in Thailand, there is very little concern regarding daily living and quality of life of these people after.leaving hospital. The major purpose of this study was to investigate the influence of the home visit programme, conducted by occupational therapists, on the functional abilities and quality of life of this group. Participants were enrolled by random sampling from Maharaj, Mckaen, and Nakornping hospitals, Chiang Mai province. These subjects were divided into two groups of 30. Group one received a home visit and was experimental, while the other group was the control. Data were collected 3 times; at discharge, and at 2 and 6 months post-discharge from hospital. The instruments used were the Test of Activities of Daily Living and World Health Organisation Quality of Life Index, Thai Version. Results demonstrated that the functional abilities in the experimental group were not significantly different while in hospital and at 2 and 6 months at home. In the control group, scores of functional abilities were lower at home than in hospital. There was no significant difference in the quality of life while at home and in hospital, in both groups. All results provided evidence for developing the home visit program to maintain and enhance the functional abilities of people with SCI, after leaving hospital. It would lead to fewer burdens on family members and society.